PELATIHAN PENYUSUNAN PROGRAM SEKOLAH ANTI BULLYING: PELATIHAN PENYUSUNAN PROGRAM SEKOLAH ANTI BULLYING - Wicaksono, Vicky Dwi; Dellarosa, Maretha; Muhimmah, Hitta Alfi; Sukartiningsih, Wahyu; Mulyani; Julianto (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
Bullying in the educational environment is in the spotlight of society and social media. Data from KPAI for 2021 recorded 2,982 cases of violence against children, of which 157 were cases of bullying. Educational institutions, as producers of human resources, are expected to create a safe and friendly environment for students, but in reality there are still many cases of bullying. Therefore, preparing an anti-bullying training program is very necessary. This training aims to equip teachers with knowledge and skills in developing a holistic anti-bullying program, creating a safe, comfortable learning environment and supporting student development. The methods used in implementing this training activity include lectures, questions and answers, discussions, giving assignments, and independent practice. The results of the training showed that teachers acquired the skills to design effective anti-bullying programs. From the pretest results, data on teacher understanding of bullying was 75.2%. After participating in the training, results increased to 80.5%. Evaluation through a training questionnaire showed that 93.5% of participants felt helped by this training. This training makes a positive contribution in creating a learning environment that is free from bullying at the elementary school level, and supports the creation of schools that are inclusive, innovative and relevant to current developments. Keywords: Program, anti-bullying, elementary school